PENGEMBANGAN E-MODUL DENGAN MENGINTEGRASI ETNOMATEMATIKA PRODUK BUDAYA JAWA TENGAH - Syafarina Nadhilah; Riawan Yudi Purwoko; Puji Nugraheni (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2020)
The purpose of this study is to determine the feasibility and produce an ethnomathematics e-module by integrating cultural products in Central Java for Junior High School students. The method used in this research is a research and development method by using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study conducts in seventh grade Junior High School in the 2019/2020 academic year. Tests and non-tests showed data collection techniques in this study in the form of a questionnaire response. The analysis technique uses the e-module feasibility analysis that meets the valid, practical, and useful criteria. The results showed that the ethnomathematics-based e-module assessment of Central Java cultural products validated by media experts, material experts, and cultural experts. In this study, ethnomathematics-based e-modules meet valid criteria with an average of 3,7. The mean score of material experts by the teacher was 3,5; material by the lecturer was 3,4; media was 3,9, and culture was 3,9. Meeting the practicality criteria was obtained from the results of the average assessment of student response questionnaires was 3,127 or 78,17% with positive response criteria, and teacher questionnaire response was 3,7 or 92,5% with very positive response criteria. Meeting the effectiveness criteria was shown based on 23 student achievement tests, 87% of students were declared complete. The ethnomathematics-based e-module of Central Java cultural products is suitable for use by Junior High School students.